2022
DOI: 10.1126/scitranslmed.abn9662
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-mediated prevention of vaginal HIV transmission is dictated by IgG subclass in humanized mice

Abstract: HIV broadly neutralizing antibodies (bNAbs) are capable of both blocking viral entry and driving innate immune responses against HIV-infected cells through their Fc region. Vaccination or productive infection results in a polyclonal mixture of class-switched immunoglobulin G (IgG) antibodies composed of four subclasses, each encoding distinct Fc regions that differentially engage innate immune functions. Despite evidence that innate immunity contributes to protection, the relative contribution of individual Ig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…This optimized AAV expression cassette resulted in several fold higher levels of bNAb expression (20–250 μg/ml) compared to nonoptimized vectors in both immunocompetent and immunodeficient mouse models [87]. We have shown that VIP is capable of protecting humanized mice from intravenous [87] as well as repeated vaginal challenges with diverse HIV strains [88,89 ▪▪ ]. Others have shown that six out of seven humanized mice could sustain suppression of HIV-1 using AAV8 to express 10-1074, an antibody targeting the V3 glycan in Env [90].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…This optimized AAV expression cassette resulted in several fold higher levels of bNAb expression (20–250 μg/ml) compared to nonoptimized vectors in both immunocompetent and immunodeficient mouse models [87]. We have shown that VIP is capable of protecting humanized mice from intravenous [87] as well as repeated vaginal challenges with diverse HIV strains [88,89 ▪▪ ]. Others have shown that six out of seven humanized mice could sustain suppression of HIV-1 using AAV8 to express 10-1074, an antibody targeting the V3 glycan in Env [90].…”
Section: Introductionmentioning
confidence: 94%
“…However, a recent study reported that VRC07-IgG2 exhibited reduced protection compared to other IgG subclasses in BLT mice. In fact, VRC07-IgG1 provided better protection relative to other IgG subclasses against vaginal challenge of HIV in BLT mice [89 ▪▪ ]. Additionally, intravenous administration of AAV8 using a liver-specific promoter to direct expression of the transgene in the liver has been reported to mitigate ADA response in macaques [98].…”
Section: Introductionmentioning
confidence: 99%
“…Mucosal immunity is critical for preventing infection, 9–11 but the efficacy of mucosal vaccination is often hampered by rapid antigen clearance at mucosal barriers. 39 Leveraging the amph-vaccine design, Hartwell et al developed amphiphile lipid-conjugated eOD-GT8 (germline-targeting engineered outer domain of HIV gp120 proteins) as an HIV mucosal vaccine (amph-eOD) 117 (Fig.…”
Section: Overview Of B Cell Responsesmentioning
confidence: 99%
“…B cells and the antibodies they produce profoundly impact many aspects of human health, such as infection, 1 inflammation, 2,3 autoimmunity, 4,5 and malignancies. 6,7 Antibodies are crucial for the neutralization and opsonization of invading pathogens during infections, 8–11 and are responsible for immune-surveillance against early carcinogenesis. 12,13 Mucosal antibodies also play pivotal roles in regulating the gut microbiome and maintaining homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…Antibody gene transfer immunoprophylaxis, which involves viral delivery of genes that encode broadly neutralizing antibodies (bNAbs), 10 , 11 , 12 , 13 , 14 , 15 has been shown to be a promising approach. Furthermore, reports have described bNAb gene delivery to stem and progenitor cells in humanized mice.…”
Section: Introductionmentioning
confidence: 99%